Psychometric Properties of a Turkish Version of the Nomophobia Scale for the Nine-Eighteen Age Group - Emine Zahide Özdemir; Murat Bektaş (Journal of Pediatric Research)

(untitled)
Aim:As a situational phobia, nomophobia is the fear experienced in the absence of a cell phone. Nomophobia leads to situations that negatively affect children’s health. The aim of this study is to conduct validity and reliability studies for the Turkish version of the Nomophobia scale.Materials and Methods:The study was conducted with volunteer students from three secondary schools and two high schools whose parents’ approval was acquired. Expert opinions, a pilot study, and a calculation of validity and reliability stages were applied. For data analysis, the Shapiro-Wilk normality test, Content Validity index, Pearson correlation analysis, Cronbach’s alpha coefficient, confirmatory factor analysis, explanatory factor analysis, and t-tests were used.Results:This study included 818 voluntary child participants. Of the participants, 56.7% were girls. In all, 91.5% of the participating children were connected to the Internet on their mobile phones, and 67.2% had their own computer. The age range of participants was 9-18 years, and their average age was 14.1±2.32 years. The scale accounts for 57.8% of the total variance. Cronbach’s alpha for the whole scale was identified as 0.90. As a result of confirmatory factor analysis, the factor coefficient was over 0.30, and the fit indices were over 0.90.Conclusion:The Turkish version of the NMP-Q is reliable and valid for the 9-18 age group.